Deregulated expression of DNA polymerase β is involved in the progression of genomic instability - Luo, Qingying (2012)
Deregulated expression of DNA polymerase beta (pol β) has been implicated in genomic instability that leads to tumorigenesis, yet the mechanisms underlying the pol β-mediated genetic instability remain elusive. In this study, we investigated the roles of deregulated expression of pol β in spontaneous and xenobiotic-induced genetic instability using mouse embryonic fibroblasts (MEFs) that express distinct pol β levels (wild-type, null and over-expression) as a model system. Three genetic instability endpoints, DNA strand breaks, chromosome breakage and gene mutation, were examined under various expression levels of pol β by comet assay, micronuclei test and hprt mutation assay. Our results demonstrate that neither pol β deficiency nor pol β over-expression is sufficient for accumulation of spontaneous DNA damage that promotes a hyper-proliferation phenotype. However, pol β null cells exhibit increased sensitivity to exogenous DNA damaging agents with increased genomic instability compared with pol β wild-type and over-expression cells. This finding suggests that a pol β deficiency may underlie genomic instability induced by exogenous DNA damaging agents. Interestingly, pol β over-expression cells exhibit less chromosomal or DNA damage, but display a higher hprt mutation frequency upon methyl methanesulfonate exposure compared with the other two cell types. Our results therefore indicate that an excessive amount of pol β may promote genomic instability, presumably through an error-prone repair response, although it enhances overall BER capacity for induced DNA damage.